Preliminary Evaluation of a Citizen Scientist Educational Curriculum Aimed at Engaging Black Men in Lung Cancer Early Detection Screening. Issue 3 (June 2022) - Matthews, Alicia K.; Murray, Marcus; Ben Levi, Josef; Odell, David; Jeremiah, Rohan; Moore, LeAndre; Oyaluade, Damilola; Chappel, Alexis; Burke, Larisa; Watson, Karriem
This article describes an educational program to engage African American men as citizen scientists (CSs) and future research partners in a lung cancer screening project. We provide an overview of the curriculum used, the structure and format of the educational sessions, and associated educational outcomes. Furthermore, we describe lessons learned in the engagement of African American men as CS in community-based lung-health equity research. The CS educational program included five group-based sessions delivered through zoom. The educational curriculum was adapted from the University of Florida Citizen Scientist program and tailored to address lung health and the contextual experiences of African American men. Each session lasted 90 minutes. Pre- and post-test measures were collected to examine changes in knowledge, comfort, health literacy, research interests, and medical mistrust. Eight African American men completed the CS educational program. Attendance rates were high for each session (100%). Seven participants completed additional human subject research certification. Improvements were observed from pre- to post-test in participants' level of knowledge, comfort, and health literacy but not medical mistrust. CS reported the most interest in participating in research aimed to identify important community strengths and problems. Study findings suggest that it was feasible to deliver an online citizen scientist educational program designed to prepare participants to serve as partners in a lung cancer screening intervention for African American men. Results suggest the educational program has the potential to improve key outcomes including completion of regulatory training and increased research-related knowledge, comfort, and health literacy.